Ethics Teaching in Education for Sustainable Development - Lars Samuelsson; Niclas Lindström (Athens Institute for Education and Research, 2022)
Education for sustainable development (ESD) is nowadays internationally considered an important aspect of the overall education of children and young people in the world. It is included among the goals of the UN 2030 Agenda for Sustainable Development. Besides its content - sustainable development - ESD is also characterized by its emphasis on a democratic and participatory educational procedure. In this paper, we show how both these aspects of ESD - its content and procedure - reveal the importance of bringing ethical considerations into ESD, as well as provide challenges for ethics teaching in ESD.